RESPON BIBIT EUCALYPTUS PELLITA TERHADAP MEDIA DAN CONTROL RELEASE FERTILIZER, HIGH YIELD TECHNOLOGY - Al Hafiz; Sulhaswardi Sulhaswardi (DINAMIKA PERTANIAN, 2014)
The purpose of this research was to know the effect of Eucalyptus pellita growth interactionally and individually on media treatment and control release fertilizer, high yield technology. The research was carried out at the R & D Nursery PT. Arara Abadi during four months, from October 2013 to January 2013. The completely Randomized Design with two factors was used. The first factor consisted of media (M) and the second factor by giving HYT (H). The parameters observed were plant height, stem diameter, number of leaves per plant, root length, root volume, biomass total, growing percentage, and seed quality. The results showed that Eucalyptus pellita gave a significant effect on treatment media interaction with control release fertilizer high yield technology for pant height with the best combination on M1H0 (26.77cm), number of eaves on M2H0 (10.87 sheets), root length on M2H0 (98.63 cm), root volume on M1H0 (4 cm3), seed quality on M1H1, M1H2, M1H3 and M2H0 (98.67%). Eucalyptus pellita affected significantly on media treatment for pant height with the best treatment on M1 (25.06 cm), stem diameter on M1 (2.60 mm), number of leaves on m1 (10.45), root volume on M1 (3.13 cm3), growing percentage on M3 (96.40%), and seed quality on M197.33%). Eucalyptus pellita showed the best response on giving control release fertilizer, high yield technology for plant height on H0 (24.57 cm), stem diameter on H0 (2.53 mm), number of leaves on H0 (10.32 sheets), root length on H4 (11.96 cm), root volume H0 (3.47 cm3), and seed quality on H0 (94.40%).